(untitled) - CHRISTIANA DEWI, EKA (LATERNE, 2012)
This research is done to know how to use playing card (remi) to improve the writing skills in German sentences. The background of this research is that the skill of complex writing due to in writing, students must competence a few elements such as vocabulary and structure, but in the reality students still get difficulties; in order need media alternative just like playing card. Keywords : Playing card, skill of writing, German sentences